Hydrologic linkages drive spatial structuring of bacterial assemblages and functioning in alpine floodplains - Freimann, Remo; Bürgmann, Helmut; Findlay, Stuart E. G.; Robinson, Christopher T. (Frontiers in Microbiology, 2015)
Microbial community assembly and microbial functions are affected by a number of different but coupled drivers such as local habitat characteristics, dispersal rates and species interactions. In groundwater systems, hydrological flow can introduce spatial structure and directional dependencies among these drivers. We examined the importance of hydrology in structuring bacterial communities and their function within two alpine floodplains during different hydrological states. Piezometers were installed in stream sediments and surrounding riparian zones to assess hydrological flows and also were used as incubation chambers to examine bacterial community structures and enzymatic functions along hydrological flow paths. Spatial eigenvector models in conjunction with models based on physico-chemical groundwater characteristics were used to evaluate the importance of hydrologically-driven processes influencing bacterial assemblages and their enzymatic activities. Our results suggest a strong influence (up to 40% explained variation) of hydrological connectivity on enzymatic activities. The effect of hydrology on bacterial community structure was considerably less strong, suggesting that assemblages demonstrate large functional plasticity/redundancy. Effect size varied between hydrological periods but flow-related mechanisms always had the most power in explaining both bacterial structure and functioning. Changes in hydrology should be considered in models predicting ecosystem functioning and integrated into ecosystem management strategies for floodplains.